ANALISIS KETERKAITAN INKLUSI KEUANGAN TERHADAP PERILAKU KEUANGAN PERSONAL MASYARAKAT DI WILAYAH KOTA DAN KABUPATEN PROVINSI JAWA TIMUR - Setiawan, Moh. Agung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The aims of this research are to determine the condition of financial inclusion in the cities and regencies in East Java province, moreover to examine and analyze the influence of index of financial inclusion on personal financial behavior. Index of financial inclusion is measured through indicators of banking penetration, accessibility of banking, and the usage of bank account. Personal financial behavior is measured by using several indicators, namely budget creating, funding (financial resources), budget allocations, expenditures, and evaluation of money usage. This type of research is explanatory with a quantitative approach. Population data in this research are 38 cities/regencies in East Java province. The sample used are 31 cities/regencies consist of 9 cities and 22 regencies were taken using stratified random sampling technique. The analytical method used is the analysis of the index of financial inclusion and simple linear regression analysis. The result of this research showed that the index of financial inclusion of each city and district in East Java province is different. The majority of cities have a high index of financial inclusion while the regencies have a low index of financial inclusion. The result also prove that the index of financial inclusion has significant positive impact on personal financial behavior. Keywords: Access of Financial Services, Index of Financial Inclusion, Financial Inclusion, Personal Financial Behavior